RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PETERNAK AYAM PADA KOPERASI SINAR MULYA MENGGUNAKAN MICROSOFT VISUAL BASIC 2010 .NET - Ade Bastian; Tri Ferga Prasetyo; Nia Kurniati (UIN Syarif Hidayatullah Jakarta, 2017)
Management information system is a system within the organization that brings daily transaction processing needs, support operations, managerial and strategic activities of an organization and provide certain outside parties with the necessary reports. Sinar Mulya Cooperative is a small cooperative whose members are small home business entrepreneurs who have stood for almost 10 years more, this cooperative initiative of small businesses that want to have association or shade where the sharing of experience between entrepreneurs engaged in the field of chicken farming in the data storage management is still not Organized or still using conventional media such as books, either books for data breeders name, drug data, ration data (feed), or chicken data. Therefore, with this application is expected to overcome the constraints experienced in obtaining information from the results of managing livestock data Chicken in improving the field of data processing chicken, chicken stock, chicken age, feed data, data drug and data breeders. The programming language used by Microsoft Visual Basic.Net 2010.